FORMULATION AND EVALUATION OF ORGANIC Xanthan Gum WITH SYNTHETIC Carbopol 940 AS UNDER EYE GEL (International Journal of Food and Nutritional Sciences, 2022)
It is a natural desire of humans to look stunning, young, and lovely. Compared toother parts of the skin, the skin surrounding the eyes is comparatively thin and has less fat. Forthis reason, puffiness, bags, pigmentation, and dark circles under the eyes are the first signs ofaging, stress, illness, environmental pollution, melanin deposition, lifestyle, and genetics.